The Influence of Workplace Branding, Company Reputation, Digital Social Platforms Information Concerning Generation Z’s Job-Seeking Behavior - Fadhila, Eka; Yafiz, Muhammad; Qarni, Waizul (Universitas Ibn Khladun Bogor, 2025)
This study aims to analyze the role of employer branding, company reputation, and media social information on the job-seeking motivation of Generation Z, with a case study of FEBI students, Department of Management, State Islamic University of North Sumatra (UINSU). Generation Z is a group of potential job seekers who have digital-native characteristics and are highly selective in choosing companies based on image, reputation, and information obtained through digital platforms. Quantitative techniques are used in this research with a survey method, and data are the analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, carried out with SmartPLS software version 4.0. The results show that the three independent variables of employer branding, company reputation, and social media information have a positive and significant effect on job application interest. The R-square value of 0.970 indicates that 97% of the variation in application interest can be explained by these three variables. These findings emphasize the need for companies to build strong employer branding, maintain a consistent reputation, and utilize social media strategically to attract the attention and interest of the younger generation. This study provides theoretical contributions to the field of human resource marketing and offers practical implications for digital recruitment strategies in the era of industry 4.0.